Activation of IL5R and CRTH2 on Human Eosinophils Elicit a Similar Molecular Response and Reveal a Synergistic Effect. Issue 1 (16th April 2018) - Sippel, Virginie; Pierlot, Gabin M.; Renault, Bérengère; Groenen, Peter M. A.; Strasser, Daniel S.
Eosinophils represent a key cell driving inflammatory processes in diseases such as asthma and eosinophilic esophagitis. The entire process of migration and activation of eosinophils is orchestrated by a myriad of molecules, among which interleukin 5 (IL5) plays a crucial role. Another receptor expressed on eosinophils is chemo-attractant receptor like expressed on Th2 cells (CRTH2). CRTH2 activation has a prominent role in stimulating Th2 and type 2 innate lymphoid cells to produce IL5 in disease tissue, but also induces eosinophils migration and adhesion. Prostaglandin D2 is the endogenous ligand of CRTH2, predominately released by activated mast cells, another key cell involved in eosinophilic diseases. Consequently, the IL5 and CRTH2 pathway are likely triggered simultaneously in eosinophils in disease tissue. Understanding the molecular effects of CRTH2 and IL5 receptor (IL5R) activated eosinophils might provide new insights for efficient eosinophils blocking. We performed gene expression profiling with isolated human eosinophils to compare the molecular signatures of CRTH2 and IL5R activation. The identified genes were confirmed using an orthogonal technology, and simultaneous IL5R and CRTH2 activation was investigated on the protein level. This study reveals that IL5R and CRTH2 activation trigger a similar molecular response in eosinophils with stronger IL5R effects. C-C chemokine ligand 2 was produced synergistically upon IL5R and CRTH2 stimulation and might contribute to monocyte and macrophage recruitment to disease tissue. The effect on C-C chemokine receptor 1 suggests that eosinophils maturation in the tissue might even occur in absence of IL5 via the CRTH2 pathway.